2019
DOI: 10.12681/jhvms.16119
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intrastromal PRP and oral doxycycline in corneal wound healing after alkali burn

Abstract: Ocular chemical burns are among the most critical and true ocular emergencies in dogs and cats, with destructive consequences on the ocular surface and intraocular tissues. Platelet alpha granules are an important reservoir of growth factors that can stimulate chemotaxis of inflammatory cells, mitosis, migration and differentiation of cells. On the other hand, tetracyclines and their derivatives exhibit non-antimicrobial properties, such as affecting inflammation, immunomodulation, cell proliferation and angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Sharaf Eldin et al [ 14 ] and Charalambidou et al [ 48 ] detected similar findings after using PRP in a rat model of corneal alkali burn, and Tanidir et al [ 49 ] reported the same in a rabbit model of corneal epithelium wound healing.…”
Section: Discussionmentioning
confidence: 64%
“…Sharaf Eldin et al [ 14 ] and Charalambidou et al [ 48 ] detected similar findings after using PRP in a rat model of corneal alkali burn, and Tanidir et al [ 49 ] reported the same in a rabbit model of corneal epithelium wound healing.…”
Section: Discussionmentioning
confidence: 64%
“…Periodontitis is a chronic inflammatory condition that develops, causing tissue damage due to prolonged inflammation and disruption of homeostasis in interaction between microorganisms and the host [1,2]. Putative pathogenic periodontal microorganisms are responsible for gingival tissue damage and disease development [3].…”
Section: Introductionmentioning
confidence: 99%